1997
DOI: 10.1177/002218569703900203
|View full text |Cite
|
Sign up to set email alerts
|

Labour-Community Coalitions and State Enterprise: the Lithgow Small Arms Factory 1918-1932

Abstract: I wish to thank the three anonymous referees of the JIR for their helpful comments. This article examines Craypo and Nissen's concept of 'labour-community' coali tions. These coalitions fight retrenchment and plant closure in small towns and cities. They can include traditional industrial relations 'actors' such as unions. Coalitions can also include groups that traditional industrial relations theory does not capture, such as the clergy, the press, politicians and local entrepreneurs. This article strengthens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Social scientists have documented organizational coalitions within virtually every individual social movement, including the environmental (Lichterman 1995;Shaffer 2000), labor (Patmore 1997;Reynolds 1999;Williams 1999), women's (Ferree and Hess 1994;Rupp and Taylor 1990;Staggenborg 1986;Whittier 1995), gay rights (Adam 1995;D'Emilio 1983), civil rights (McAdam 1982;Morris 1984), and nuclear freeze (Hathaway and Meyer 1993;Rochon and Meyer 1997) movements. Research demonstrates that coalitions are more likely to form when a movement faces increased political opportunities or threats (Hathaway and Meyer 1993;McCammon and Campbell 2002;Rochon and Meyer 1997;Staggenborg 1986), when resources are plentiful (DiazVeizades and Chang 1996;Staggenborg 1986;Williams 1999;Zald and McCarthy 1987), and when there are no signi cant identity differences between the groups involved (Arnold 1995;DiazVeizades and Chang 1996;Lichterman 1995;McCammon and Campbell 2002).…”
mentioning
confidence: 99%
“…Social scientists have documented organizational coalitions within virtually every individual social movement, including the environmental (Lichterman 1995;Shaffer 2000), labor (Patmore 1997;Reynolds 1999;Williams 1999), women's (Ferree and Hess 1994;Rupp and Taylor 1990;Staggenborg 1986;Whittier 1995), gay rights (Adam 1995;D'Emilio 1983), civil rights (McAdam 1982;Morris 1984), and nuclear freeze (Hathaway and Meyer 1993;Rochon and Meyer 1997) movements. Research demonstrates that coalitions are more likely to form when a movement faces increased political opportunities or threats (Hathaway and Meyer 1993;McCammon and Campbell 2002;Rochon and Meyer 1997;Staggenborg 1986), when resources are plentiful (DiazVeizades and Chang 1996;Staggenborg 1986;Williams 1999;Zald and McCarthy 1987), and when there are no signi cant identity differences between the groups involved (Arnold 1995;DiazVeizades and Chang 1996;Lichterman 1995;McCammon and Campbell 2002).…”
mentioning
confidence: 99%
“…They, too, underplay the possibility of new union forms. Drawing mainly on literature from the United States (Craft 1990;Craypo & Nissen 1993), it has been suggested that under some circumstances unions can build alliances with other groups in particular places around particular issues, most notably service delivery and plant closures (Patmore 1997;Thornthwaite 1997;Labour History 2000). However, there has been considerable skepticism about advancing beyond such ad hoc alliances.…”
Section: Geographies Of Work Community and Unionismmentioning
confidence: 99%
“…Most analyses have focused on 'labour-community coalitions', rather than community unionism as such. Drawing mainly on literature from the USA (see especially Craft 1990;Craypo & Nissen 1993), it has been suggested that unions can build successful alliances with other groups in particular places around particular issues, most notably service delivery and plant closures (Patmore 1997;Thornthwaite 1997).…”
Section: B Ellemmentioning
confidence: 99%